Accommodation problems of women factory workers : a case study of the Katunayake Export Processing Zone in Colombo, Sri Lanka - Piyaratne, P. K.; Kioe-Sheng, Yap; Wickramanayake, B.W.E.; Amin, A.T.M. Nurul; Lefebvre, Bernard G.; The Royal Netherlands Government (Bangkok : Asian Institute of Technology, 1990)
The convergence of young migrant labour for the job opportunities in the Export Processing Zone at Katunayake (KEPZ) has created a large demand for accommodation in the villages around the Zone. Severe norms of punctuality and low wages in the factories together with the irregular transport service in the area force the migrants to stay in whatever housing is available at low rents in the area close to the industrial zone. The supply of housing and facilities to meet the large demand of the workers puts a heavy pressure on the existing housing stock in the villages situated in a limited area and in turn results in over-crowded, sub-standard rental housing with poor facilities. A segment of the over- crowded workers houses in five villages located close to the industrial zone was studied. Five types of housing available for accommodation of workers were identified such as private dormitory, rental room, rental house, company hostel and institutional hostel, and observed in terms of housing conditions and facilities available in each. A sample of women workers who were renting accommodation in those houses was interviewed to ascertain their problems while living in such houses. In addition, various parties which are responsible and presently involved in the provision of housing for the workers were studied namely a sample of private land and house owners in the area, the government institutions, the industrialists in the KEPZ and NGOs. The results show that an alarming situation is existing in two types of housing, namely private dormitories and rental rooms in which workers are undergoing numerous hardships. Upgrading and increasing the existing supply of housing through the encouragement of the private sector in the area are two ways of solving the problem, but it is l ikely to be imprac ticable given the high cost of construction and the low affordability of workers. Therefore, a multi- level approach of all participants, such as the government, industrialists, private sector and workers would be a better solution for the problem of housing of the workers.
A thesis submitted in partial fulfillment of the requirements for the award of the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1990
Keywords: Labor and laboring classes -- Dwellings -- Sri Lanka